Bilingual school education with spoken and signed languages in Europe. Issue 5 (28th May 2022) - Krausneker, Verena; Becker, Claudia; Audeoud, Mireille; Tarcsiová, Darina
ABSTRACT: At least since the UN Convention on the Rights of People with Disabilities, deaf children worldwide have a right to education not only in the spoken and written language of their country, but also in the national sign language. The pedagogical use of a sign language in European schools for the deaf began in the 1980s and has since evolved significantly. This paper presents a survey of 39 European countries that documents the status of bimodal bilingual education using a spoken and a signed language. Data was collected through an expert survey on the three dimensions policies, practices and cultures of bimodal bilingual education and an analysis of relevant legal documents. The results reveal that bimodal bilingual education is increasingly implemented in deaf education but is not fully established all over Europe. In many countries, bimodal bilingual education is limited to special schools and is rarely offered in inclusive mainstream schools. Implementation processes are similar across Europe: Programmes are primarily initiated by parents, teachers or the deaf community but educational policies lag behind the practices at schools. Legal foundations (e.g. curricula and professionalization for the use of sign languages) guarantee the sustainability and quality of bimodal bilingual education.